Using Game Design to Teach Informatics and Society Topics in Secondary Schools - Kayali, Fares; Schwarz, Vera; Purgathofer, Peter; Götzenbrucker, Gerit (Multimodal technologies and interaction, 2018)
This article discusses the use of game design as a method for interdisciplinary project-based teaching in secondary school education to convey informatics and society topics, which encompass the larger social context of computing. There is a lot of knowledge about learning games but little background on using game design as a method for project-based teaching of social issues in informatics. We present the results of an analysis of student-created games and an evaluation of a student-authored database on learning contents found in commercial off-the-shelf games. We further contextualise these findings using a group discussion with teachers. The results underline the effectiveness of project-based teaching to raise awareness for informatics and society topics. We further outline informatics and society topics that are particularly interesting to students, genre preferences, and potentially engaging game mechanics stemming from our analyses.